ANALISIS LIKUIDITAS, PROFITABILITAS, LEVERAGE, DAN AKTIVITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2015-2017 - Dwi setiyawan, 15.05.52.0111; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2019)
This study aims to test the liquidity ratio, profitability, leverage, and activity on the value of the company and test which factors of the ratio are the most influential on the value of the company. Research methods used quantitative methods. This study uses financial statements of manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017 with a sample of 180 companies. The analysis method used in this study is the Multiple Linear Regression Test. The results of the study show that partially only Profitability and Leverage have a significant influence on Company Value with a significance level of 0,000 and 0,017. While Liquidity and Activities that have a non-significant effect on Company Values with a significance level of 0.162 and 0.701. Second, simultaneous tests show that Liquidity, Profitability, Leverage, and Activity together have a significant effect on firm value.